Agro‐climate services and drought risk management in Jamaica: A case study of farming communities in Clarendon Parish. Issue 1 (5th January 2022) - Buckland, Sarah; Campbell, Donovan
Abstract : For many generations, Caribbean smallholder farmers have used traditional knowledge to manage drought impacts. However, patterns of increased climate variability increasingly challenge traditional drought management practices, creating livelihood insecurities and uncertainties. Climate Information Services (CIS) have been promoted as an agile risk management strategy to help farmers negotiate challenges of increased climate extremes. Yet, despite the promise and possibilities of CIS, there is limited evidence of CIS uptake and associated risk reduction across the Caribbean. A mixed‐method research approach is used to examine the uptake of CIS among farmers (N = 356), testing the association with selected drought impact outcomes in one of Jamaica's breadbasket regions. The associations between drought impacts and farmer accessibility and use of four (4) locally available CIS are assessed. Results indicate limited farmer uptake of mobile text and online climate information products, with less than 5 per cent of the sample having accessibility to online CIS. Farmers who are aware of, and use CIS, reported lower crop losses, less financial strain, and were more likely to reinvest immediately after drought events. These results provide empirical evidence of associations between farm‐level use of CIS and drought risk management actions, which could be used to inform future drought management interventions.